Constantinople 1453 the end of Byzantium - Nicolle, David 1944- (Campaign (Osprey Publishing), 2000)
This Osprey title details the epic four-month siege of the city of Constantinople in 1453, last vestige of the once mighty Roman and Byzantine Empires. Mehmet 'The Conqueror' led an army of 80,000 men with a massive siege train against the city. Defending were a mere 10,000 men under the Emperor Constantine XI. The Turkish artillery battered the ancient city walls mercilessly, levelling a large section. A gallant defence held off the massive Turkish assault for several hours. Refusing appeals to flee, Constantine returned to the breaches and fought until overwhelmed and killed. Thus died the last Emperor of the Byzantines, and with him his once glorious empire.